Embryo Transfer in Angus and Brahman Recipient Cows: Effect of Two Methods of Estrus Synchronization on Induced Estrus and Pregnancy - Chase, Chad; Vargas, Carlos; Hammond, Andrew; Olson, Timothy; Griffin, James; Murphy, Clifton; Tewolde, Assefaw; Fields, Michael (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Over a 3-year period, 88 Angus and 87 Brahman cows were used as recipients to determine the effects of breedtype and method of estrous synchronization on induced estrus and subsequent pregnancy following embryo transfer. Estrus was synchronized in recipients using either prostaglandin-F2_ (PGF; Lutalyse) or progestogen (PRO; Syncro-Mate-B). Recipients were treated (im) with PGF on day -11 (25 mg), 0 (12.5 mg), and 1 (12.5 mg). Recipients were treated with PRO on day -9 (6 mg norgestomet ear implant and 2 mL [im] of 3 mg of norgestomet and 5 mg of estradiol valerate) and the ear implant was removed on day 0. Embryos were randomly transferred to recipients synchronous +24 to -24 h with a 7-d embryo. Both synchronization methods (PGF vs. PRO) were similarly effective in inducing estrus (89.8 vs. 86.7%). Percentage of induced estrus was similar between Brahman (91.0%) and Angus (85.6%). Recipients treated with PGF had a longer (P = 0.001) interval to estrus than PRO treated recipients (77.4 vs. 60.1 h). Estrus response in Angus was earlier (P = 0.043) than in Brahman (65.4 vs. 72.2 h). Neither breed (P = 0.97; Angus 49% 35/72 and Brahman 54% 38/70) nor estrus synchronization treatment (P = 0.23; PRO 49% 35/72 and PGF 54% 38/70) affected pregnancy rate. Pregnancy rates in recipients closely synchronized (0 h) was 60.0%, within +12 and -12 h was 56.0%, and within +24 and -24 h was 51.5%. Four-year-old recipients had lower pregnancy rates (34.8%) than did 5-year-old (60.9%) or greater than 6-year-old (70.0%) recipients. These results indicate that PGF, when administered as a split-second dose, is as effective in synchronizing estrus in Angus and Brahman as PRO. Asynchrony of embryo age with recipient stage of cycle up to +24 or -24 h did not significantly affect pregnancy rates.